Factorial validity of the Childhood Trauma Questionnaire in Italian psychiatric patients. (30th November 2016) - Innamorati, Marco; Erbuto, Denise; Venturini, Paola; Fagioli, Francesca; Ricci, Federica; Lester, David; Amore, Mario; Girardi, Paolo; Pompili, Maurizio
Abstract: Early adverse experiences are associated with neurobiological changes and these may underlie the increased risk of psychopathology. The Childhood Trauma Questionnaire (CTQ-SF) is the most commonly used instrument for assessing childhood maltreatment. Thus, the aim of our study was to investigate the factorial validity of an Italian version of the CTQ-SF in a sample of psychiatric inpatients by means of confirmatory and exploratory factor analyses. The sample was composed of 471 psychiatric in-patients and out-patients (206 males and 265 females) aged 16–80 years (mean age=34.4 years [SD=16.3]) consecutively admitted to two psychiatric departments. All patients were administered the Italian version of the CTQ-SF. We tested five different factor models which lacked good fit, while the exploratory factor analysis supported the adequacy of a solution with three factors (Emotional Neglect/Abuse, Sexual Abuse, Physical Neglect/Abuse). The three factors had satisfactory internal consistency (ordinal Cronbach alphas >0.90). Our study supports results from previous research indicating the lack of structural invariance of the CTQ-SF in cross-cultural adaptations of the test, and the fact that, when measuring different types of childhood maltreatment, the difference between abuse and neglect may be not valid. Highlights: Examined factor validity of the Italian version of the CTQ-SF. Five models previously reported in the literature did not fit the data. The exploratory factor analysis supported a three-factor solution. When using the CTQ-SF the difference between abuse and neglect may be not so clear.